Bio-monitoring selected heavy metal concentration in Nerita sp. collected from Tanjung lumpur mangrove forest. - Mohd Dom, Azratul Ashimah Nur; John, Akbar; Yunus, Kamaruzzaman; I. Sheikh, Hassan; Khan Chowdhury, Ahmed Jalal; Nordin, Noor Faizul Hadry (Razi Publishing, 2017)
Environmental pollution by heavy metals is a serious threat to human and ecosystem. Accumulation of heavy metals in the biota may pose hazardous impact on public health and other living organisms. By using gastropods Neritasp as bio-indicator, the levels of heavy metals in their soft tissues can determine the contamination of heavy metals in the Tanjung Lumpur Mangrove along the Kuantan River. The aim of this study is to identify copper, cadmium, chromium and iron accumulated in the tissue of Neritasp, to investigate the concentration of the copper, cadmium, chromium and iron in the molluscan tissue among the different sizes of gastropod Neritaspand to compare the concentrations of heavy metals in a gastropod Neritasp tissue among the different stations of Kuantan River, Pahang. Gastropods of Neritasp were randomly collected along the river. The tissues of gastropods were digested with nitric acid. Then, concentration of copper, cadmium, chromium and iron were analyzed by using flame atomic absorption spectrophotometer (AAS) model Perkin Elmer SIMAA 6100 graphite furnace. Neritasp accumulate copper the most in their tissues compared to other heavy metals. The concentrations are around 189.8 µg/ L – 247.95 µg/ L. The highest concentration of copper is in Station 3 which is at 241.67 µg/ L. The second highest concentration is iron or ferrum where the concentrations are around 121.25 µg/ L – 174.55 µg/ L. Station 3 was identified to have the highest concentration of iron at 161.12 µg/ L. Followed by, chromium which the concentrations are around 23.49 µg/ L – 46.15 µg/ L. The highest concentration of chromium is Station 1 at 34.82 µg/ L. The lowest concentration of heavy metals is cadmium which is around 8.69 µg/ L – 18.46 µg/ L. Also, Station 1 showed the highest concentration of cadmium at 17.56 µg/ L. This study can be used to identify contamination of heavy metals in marine zone by using bio-indicator to avoid environmental perturbation.